Utilizing TikTok to Foster Personal Character Elements of Faith, Piety to God Almighty, and Noble Character in Phase C Elementary School Students - Rahayu, Modhi; Purnamasari, Iin; Saputra, Henry Januar (Indonesian Academy of Social and Religious Research (IASRR), 2024)
The decline in human dignity (dehumanization) is evident in the widespread use of social media platforms like TikTok, including among elementary school students. Many children enjoy using TikTok, which affects their personal character. It is necessary to examine the impact of TikTok usage on elementary school students to develop strategies for teachers to ensure safe TikTok use. This study focuses on analyzing the impact of TikTok usage on the personal character elements of faith, piety to God Almighty, and noble character in Phase C elementary school students. The objectives of this research are to analyze the influence of TikTok usage, examine the intensity of TikTok usage, assess the information shared on TikTok, and design strategies for teachers to guide students' TikTok usage. This research is a descriptive qualitative study with a phenomenological approach. Data were collected using triangulation techniques, including observation, questionnaires, interviews, and documentation. The results indicate that TikTok usage has both positive and negative impacts on the personal character elements of Phase C students. Positively, students became more active, expressive, confident, communicative, creative, and gained updated knowledge through TikTok. However, negative impacts include increased laziness, loss of manners, emotional instability, lack of responsibility, and diminished concern for the environment. To maximize the positive and minimize the negative impacts of TikTok, it is crucial to implement control and wise supervision in digital etiquette.